Skrining Fitokimia Ekstrak Metanol Karang Lunak Lobophytum sp. - M. Nur, Risna; Hala, Yusminah; Muâ€™nisa, Andi (bionature, 2019)
Abstract. Soft corals produce several bioactive compounds that can be used. One of the soft corals that has the potential to produce bioactive compounds is lobophytum sp.. The purpose of this study was to determine the chemical component of the soft coral lobophytum sp. . Sample extraction was done by the using of macerationmethod with methanol solvent.Theobtainedextract then tested for its chemical component. The chemical component that tested in this study were alkaloids, flavonoids, triterpenoids/ steroids, tanins and saponins. The results showed that the soft coral lobophytum sp. contains some chemical componentssuch as alkaloids, flavonoids, triterpenoidsÂ  and saponins.Keywords: soft coral, lobophytum, chemical component.